Diagnostic accuracy of two-dimensional shear wave elastography and point shear wave elastography in identifying different stages of liver fibrosis in patients with metabolic dysfunction-associated steatotic liver disease: A meta-analysis - Xiangyi Xu; Yiqing Zhang; Qiwei Zhu; Yuchen Xie; Yuanyuan Zhou; Bingtian Dong; Chaoxue Zhang (Biomolecules & Biomedicine)
To assess the diagnostic accuracy of two-dimensional shear wave elastography (2-D SWE) and point shear wave elastography (pSWE) in detecting liver fibrosis stages in patients with metabolic dysfunction-associated steatotic liver disease (MASLD), a comprehensive search was conducted across four databases up to February 9, 2024. A bivariate random-effects model was used to analyze the diagnostic accuracy of the methods. After screening, thirteen studies involving pSWE included 1,527 patients, while nine studies involving 2-D SWE included 1,088 patients. The areas under the summary receiver operating characteristic (SROC) curves for diagnosing significant fibrosis (F≥2), advanced fibrosis (F≥3), and cirrhosis (F=4) using pSWE and 2-D SWE were as follows: 0.84 (95% CI 0.80-0.87), 0.91 (95% CI 0.88-0.93), and 0.94 (95% CI 0.91-0.95) for pSWE; 0.83 (95% CI 0.79-0.86) 0.85 (95% CI 0.82-0.88), and 0.89 (95% CI 0.86-0.91) for 2-D SWE, respectively. The pooled sensitivity for pSWE and 2-D SWE for stages F≥2, F≥3, and F=4 were 0.71 (95% CI 0.63-0.78), 0.81 (95% CI 0.72-0.88), and 0.81 (95% CI 0.63-0.91) for pSWE, and 0.77 (95% CI 0.68-0.84), 0.80 (95% CI 0.72-0.87), and 0.92 (95% CI 0.75-0.98) for 2-D SWE, respectively. The pooled specificity of pSWE and 2-D SWE for these stages were 0.83 (95% CI 0.76-0.88), 0.87 (95% Cl: 0.81-0.92), and 0.91 (95% CI 0.86-0.94) for pSWE, and 0.76 (95% CI 0.66-0.84), 0.76 (95% CI 0.69-0.82), and 0.83 (95% CI 0.78-0.85) for 2-D SWE, respectively. In conclusion, both 2-D SWE and pSWE demonstrated high diagnostic performance in identifying various stages of liver fibrosis in MASLD patients.